Light-Induced Degradation of Thin Film Silicon Solar Cells. (January 2016) - Hamelmann, F U; Weicht, J A; Behrens, G
Abstract: Silicon-wafer based solar cells are still domination the market for photovoltaic energy conversion. However, most of the silicon is used only for mechanical stability, while only a small percentage of the material is needed for the light absorption. Thin film silicon technology reduces the material demand to just some hundred nanometer thickness. But even in a tandem stack (amorphous and microcrystalline silicon) the efficiencies are lower, and light-induced degradation is an important issue. The established standard tests for characterisation are not precise enough to predict the performance of thin film silicon solar cells under real conditions, since many factors do have an influence on the degradation. We will show some results of laboratory and outdoor measurements that we are going to use as a base for advanced modelling and simulation methods.